2015
DOI: 10.1055/s-0035-1555150
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Diplopia after Rapid Maxillary Expansion: A Clue to Underdiagnosed Pseudotumor Cerebri Syndrome?

Abstract: Rapid maxillary expansion (RME) is an orthodontic procedure that separates the two maxillary bones at the mid palatine suture level. RME is commonly used in the pediatric age group to reduce and/or eliminate a transverse maxillary deficiency. At our institution we followed up an 11-year-old adolescent who was diagnosed with a class III malocclusion and was treated by RME with the combined use of expansion appliances (i.e., Hyrax) in addition to maxillary protraction devices (i.e., Delaire facemask). Three mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In a case report, it was reported that RME treatment may cause raised intracranial pressure in patients with impaired venous drainage and pseudotumor cerebri syndrome (PTCS) by affecting cerebral venous circulation on MRI. 7 In our current investigation, there was a notable increase in ONSD one minute after screw activations (T1, T5) in comparison to the ONSD values prior to screw activations (T0, T4) (p=0.001). While the precise mechanisms underlying the elevation of ICP are not yet fully understood, we speculate that this phenomenon might be attributed to varying levels of stress and cerebral hemodynamic alterations within the intracranial region.…”
Section: Discussionsupporting
confidence: 42%
See 2 more Smart Citations
“…In a case report, it was reported that RME treatment may cause raised intracranial pressure in patients with impaired venous drainage and pseudotumor cerebri syndrome (PTCS) by affecting cerebral venous circulation on MRI. 7 In our current investigation, there was a notable increase in ONSD one minute after screw activations (T1, T5) in comparison to the ONSD values prior to screw activations (T0, T4) (p=0.001). While the precise mechanisms underlying the elevation of ICP are not yet fully understood, we speculate that this phenomenon might be attributed to varying levels of stress and cerebral hemodynamic alterations within the intracranial region.…”
Section: Discussionsupporting
confidence: 42%
“…6,11,19 Importantly, the strain exerted around various cranial base foramina can lead to the enlargement of adjacent blood vessels. 7 In a study on rabbits by Li et al 6 , it was reported that anatomical stresses on craniofacial structures during RME therapy cause cerebral hemodynamic changes, including increases in CBF and CBV. In a case report, it was reported that RME treatment may cause raised intracranial pressure in patients with impaired venous drainage and pseudotumor cerebri syndrome (PTCS) by affecting cerebral venous circulation on MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that maxillary disjunction generates strains and stresses in the cranial structures, especially in the zygomatic arch (29), as it represents a buttress of great resistance against maxillary expansion with high tension exerted in the orbit of the unpaired sphenoid bone, orbital ssure, and the pterygoid processes (30). Headache and diplopia due to increasing intracranial pressure (pseudotumor cerebri syndrome) have been reported (31). Moreover, in both groups even with rapid activation distance between both optic foramen and both pterygoid canals do not change between T1/T2 (Table 1).…”
Section: Formularendementioning
confidence: 99%